2014
DOI: 10.4172/2329-9096.s3-008
|View full text |Cite
|
Sign up to set email alerts
|

A New Idea for Stroke Rehabilitation: Bilateral Transfer Analysis from Healthy Hand to the Paretic One with a Randomized and Controlled Trial

Abstract: Background: Bilateral transfer of a motor skill is a phenomenon according to which, one hand can "teach" a skill to the other hand. In this research, controlled and randomized, we tested the ability of bilateral transfer (BT) to improve the coordination of the paretic hand in patients that suffered a stroke, with the aim of restricting the field for further research on the impact of BT in rehabilitation, we analyzed the differences in the expression of BT phenomenon among sexes and side of hemyparesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
2
0
2
Order By: Relevance
“…The changes of the contralateral limb motions demonstrate the phenomenon of reciprocal two-way character influence between affected side and contralateral side. This is consistent with the earlier studies [24,25].…”
Section: Dynamics Of the Function Of The Shoulder Joint And Shoulder supporting
confidence: 94%
“…The changes of the contralateral limb motions demonstrate the phenomenon of reciprocal two-way character influence between affected side and contralateral side. This is consistent with the earlier studies [24,25].…”
Section: Dynamics Of the Function Of The Shoulder Joint And Shoulder supporting
confidence: 94%
“…This phenomenon has been studied in stroke individuals with positive results. Ausenda et al [ 25 ] have found evidence that the BT of motor skills is present in post-stroke individuals, and that it improves the ability of the affected hand in performing a task. They investigated BT using a “nine hole peg test” and found some interesting results, e.g., the execution speed of the nine hole peg test with the paretic hand, after training the non-paretic hand, was on average more than 22% faster than the value recorded at baseline.…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral transfer (BT) occurs in the stroke patients with the same phenomenon features as noted in the healthy individuals, with a higher incidence among men and a bigger effect when the trained healthy hand is the dominant one, to the paretic non-dominant hand. 15 Most subjects in this study are sub-acute patients (64%). Early after the stroke onset or in an acute setting, the patients need to be properly managed considering the emergency condition of admission to morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%